2001
DOI: 10.1021/jo001393n
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselectivity of Captodative Olefins in 1,3-Dipolar Cycloadditions. A DFT/HSAB Theory Rationale for the Observed Regiochemistry of Nitrones

Abstract: Captodative olefins 1-acetylvinyl carboxylates proved to be highly regioselective dipolarophiles in 1,3-dipolar cycloadditon to propionitrile oxide, arylphenylnitrile imines, diazoalkanes, and nitrones to yield the corresponding 5-substituted heterocycles. The addition of the latter was also stereoselective, being slightly susceptible to steric demand of the carboxylate substituent in the olefin. All atempts to cleave the isoxazolidine N-O bond under reductive conditions failed, providing diverse products with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 96 publications
5
29
0
2
Order By: Relevance
“…[28] They showed that regioselectivity is controlled because the electron-donating groups in the captodative olefins increase the interaction between the nitrone carbon atom and the b-C1 carbon of the a,b-unsaturated ketone. This subtle stereoelectronic effect was reflected in the electrophilic attack values of the nitrone carbon atom and the C1 atom of the captodative olefins.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 99%
“…[28] They showed that regioselectivity is controlled because the electron-donating groups in the captodative olefins increase the interaction between the nitrone carbon atom and the b-C1 carbon of the a,b-unsaturated ketone. This subtle stereoelectronic effect was reflected in the electrophilic attack values of the nitrone carbon atom and the C1 atom of the captodative olefins.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30] Ten years ago, Tanaka et al 17 examined the 1,3-DC of 3,4-dihydroisoquinoline N-oxide to methyl 2-butenoate. The authors proposed a concerted mechanism with a nonsymmetric transition state in which the C-O bond is formed to a greater degree than the C-C one.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, analysis of the most electrophilic center of the electrophile and the most nucleophilic center of the nucleophile accounts for the regioselectivity in these polar processes. 23 To put in evidence the preferential cyclization mode and consequently the major cycloadducts of 1,3-dipolar cycloaddition reactions under investigation, we will consider two-center Table 1 Energies of reactives, transition states and cycloadducts 3, 4, 5 and 6, E (a.u. ), relative activation energies ∆E a (kJ•mol -1 ) and relative energies between products and reactives, ∆E r (kJ•mol…”
Section: Resultsmentioning
confidence: 99%